Prospective Randomized Observational Pilot Trial Evaluating the Effect of Different Durations of Interdisciplinary Early Intervention and Family Support in Parents of Very Low Birth Weight Infants (Early Bird Study) - Bernhard Resch; Bernhard Resch; Bernhard Resch; Claudia Hofbauer-Krug; Claudia Hofbauer-Krug; Jasmin Pansy; Karin Prechtl; Alexander Avian; Ronald Kurz; Ronald Kurz (Frontiers Media S.A., 2020)
Background: Early childhood intervention (ECI) is a holistic approach for infants with or at risk for psychomotor and/or cognitive and/or behavioral impairment. It aims to optimally support them and positively influence their neurodevelopmental outcome. The right dosage of intervention and when the intervention should start are still to be determined. Hypothesis: Parents are more satisfied when the duration of ECI is longer (120 min once a week) than the usual 90-min session.Methods: We developed a parental questionnaire (both mother and father) that evaluated the level of satisfaction of parents with the intervention. We compared 120 with 90 min of ECI per week during the school year 2017/18. Included were parents of very low birth weight infants (<1,500 g) following informed consent. ECI was initiated at the NICU at an infant age of ≥ 2 weeks. Parents were randomized (https://www.randomizer.at/) to a 120- or 90-min duration and had to answer the questionnaire to the approximate time-point of 1, 3, and 6 months. Answers were classified as strongly agree, agree, neither agree nor disagree, disagree, and strongly disagree except for the last question, which directly rated the ECI professional.Results: Eleven fathers (55%) and 19 mothers (95%) of the 10 parents of each group participated in the study. Demographic data did not differ between groups, and the median time-points of questionnaire answers were 77, 137, and 220 days, respectively. Overall, 120-min ECI sessions were not superior to 90-min sessions for both parents regarding parental satisfaction during the study time. We found no differences between fathers and mothers and minimal changes over time. All parents were satisfied with the ECI professionals, irrespective of ECI duration.Conclusion: An ECI duration of 120 min once per week was not superior to a 9- min duration regarding parental satisfaction with ECI professionals and their work.